DESIGN STUDY OF MODULAR NUCLEAR POWER PLANT WITH SMALL LONG LIFE GAS COOLED FAST REACTORS UTILIZING MOX FUEL - ILHAM (NIM : 10211078), MUHAMMAD
Growing energy, needed as equal as increasing number of the world's population, encourages the development of technology and science for creating new energy sources producing the technology of nuclear power plants (NPP) for generate considerable amount of thermal energy. In this research, we will conduct a neutronic analysis of Gas Cooled Fast Reaktor (GCFR) generation IV with characteristics small long life reactor. Modeling system design of GCFR using SRAC program (Standard Thermal Reaktor Analysis Code) for neutronic analysis. Study design of fast reaktors GCFR using Mixed Oxide fuel (MOX) with adding Neptunium-237 for lower initial excess reactivity and long life reactor, Helium as a coolant with the variation of thermal power 100-500 MWth and fuel fraction 45-70%. With cylindrical pin cell and cylindrical balance of reactor core geometry, the core subdivided into four regions in radial direction with three regions belong to fuel with different percentages of plutonium and one to reflector. The variation of percentages of plutonium are 7-15%. The obtained results are the effective multiplication factor (K-eff) and density value of core reactor power. Based on the calculation result of optimum design reactor, which can be operated over 20 years with excess reactivity under 3%. The obtained of optimum power is 200 MWth with 60, 55, 55% of fuel fraction in each region and 10.5, 12, 13.5% of Plutonium percentages in each region with percentages of Neptunium-237 is 12.5%.